Electrochemically Growth of Pd Doped ZnO Nanorods on QCM for Room Temperature VOC Sensors - Öztürk, Sadullah; Kösemen, Arif; Kösemen, Zühal Alpaslan; Kılınç, Necmettin; Öztürk, Zafer Ziya; Penza, Michele (Elsevier, 2016)
Pristine and various palladium (Pd) doped ZnO nanorods have been synthesized on the quartz crystalmicrobalance (QCM) for volatile organic compound (VOCs) sensors at room temperature. The dopingconcentrations were varied from 0 mol% to 2.5 mol% by using electrochemical deposition method. Thediameters of the fabricated nanorods were in the range of 100–200 nm, and were increased with Pddoping. The tested VOCs included alcohols (ethanol, methanol, isopropyl), ester (ethyl acetate), aromatic(toluene, xylene), ketone (acetone) and chloroform in the different concentrations. The results indicatedthat the sensitivity of the sensing materials was enhanced with the increasing Pd doping concentrationsexcept for the acetone and chloroform. The undoped ZnO nanorod sensor showed higher sensor responseagainst to acetone and chloroform while exposing high concentration of two analytes due to the absorb-ing/adsorbing mechanism. All undoped and Pd doped nanorods sensors showed the highest sensitivityto xylene.
Keywords: Gas Sensor; ZnO; Nanorods; Electrochemical Deposition; Pd Doping; VOCs; QCM